1986
DOI: 10.3181/00379727-181-42221
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure of Sinoaortic-Denervated Dogs Is Not Increased by Cardiac Denervation

Abstract: Although blood pressure rises markedly after acute sinoaortic denervation, animals with chronic sinoaortic denervation have normal or only slightly elevated mean arterial pressures. The present study was performed to determine whether reflexes from cardiac receptors exert antihypertensive effects and thereby lower blood pressure in animals with chronic sinoaortic denervation. We made multiple measurements of blood pressures in dogs with chronic sinoaortic denervation before and after their hearts were denervat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…baroreceptor denervation (Ferrario et al 1969, Cowley et al 1973, Ito & Scher 1981, Cornish & Gilmore 1983, Persson et al 1988, Ramirez et al 1985, Geer et al 1986, Trapani et al 1986, Alper et al 1987, Bishop et al 1987. Arterial baroreceptor denervated animals also develop hypertension during the immediate postdenervation period (Ferrario et al 1969;Cowley Correspondence: Dr Pontus B. Persson, I. Physiologisches Institut, Universitat Heidelberg, Im Neuenheimer Feld 326, D-6900 Heidelberg, W. Germany.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…baroreceptor denervation (Ferrario et al 1969, Cowley et al 1973, Ito & Scher 1981, Cornish & Gilmore 1983, Persson et al 1988, Ramirez et al 1985, Geer et al 1986, Trapani et al 1986, Alper et al 1987, Bishop et al 1987. Arterial baroreceptor denervated animals also develop hypertension during the immediate postdenervation period (Ferrario et al 1969;Cowley Correspondence: Dr Pontus B. Persson, I. Physiologisches Institut, Universitat Heidelberg, Im Neuenheimer Feld 326, D-6900 Heidelberg, W. Germany.…”
mentioning
confidence: 99%
“…Arterial baroreceptor denervated animals also develop hypertension during the immediate postdenervation period (Ferrario et al 1969;Cowley Correspondence: Dr Pontus B. Persson, I. Physiologisches Institut, Universitat Heidelberg, Im Neuenheimer Feld 326, D-6900 Heidelberg, W. Germany. et al 1973, Geer et al 1986, Persson 1988), but it is controversial whether this hypertension is sustained. Some investigators found a chronic increase in arterial blood pressure (Bishop et al 1987, Ito & Scher 1981, Laubie & Schmitt 1979, whereas others observed a subsequent normalization after denervation (Cowley et al 1973, Cornish & Gilmore 1983, Ramirez et al 1985, Geer et al 1986, Saito et al 1986, Persson 1988.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important for the interpretation that these were acute experiments and that baroreceptor afferents are also interrupted by the cold-block of the vagi. With respect to the arterial baroreceptors, it is a well established fact that an acute interruption of their afferents produces a transient hypertension over the following hours (Walgenbach 1984), up to the next week (Geer et al 1986, Kezdi et al 1980. This artifact underlies cold-block investigations.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge complete, long-term denervation of the cardiopulmonary area has not been performed in conscious dogs, although others have described similar approaches denervating arterial baroreceptor (It0 & Scher 1979, Cowley et al 1980, and intersecting cardiac branches (Gregg et al 1972, Geer et al 1986, Noble et al 1972). The present study was therefore designed to investigate the longterm changes in cardiovascular function, plasma renin activity and blood volume control, before and after the complete denervation of the cardiopulmonary area.…”
Section: P Persson Et Almentioning
confidence: 99%